Global trends in the burden of non-Hodgkin Lymphoma: a comprehensive analysis from 1990 to 2045 - Shuangling Wang; Jun Wang; Jianxiong Lin (Cancer Causes & Control, 2026)
Purpose To analyze global trends in the non-Hodgkin lymphoma (NHL) burden from 1990 to 2021 and forecast future trajectories from 2022 to 2045. Methods Using data from the GBD 2021 Study, we extracted age-standardized incidence, mortality, and disability-adjusted life year (DALY) rates and estimated their average annual percent changes (AAPCs). Age-period-cohort models were constructed to assess temporal trends, and decomposition analysis identified drivers of burden changes. Future projections were generated using the Nordpred model. Results From 1990 to 2021, the global incidence of NHL increased (AAPC = 0.53; 95% CI: 0.50–0.56), whereas mortality (AAPC = – 0.41) and DALY rates (AAPC = – -0.60) decreased. Aging accounted for 35% of incident cases, population growth accounted for 49%, and epidemiological changes accounted for – 14%. By 2045, projected cases, and deaths are expected to reach 985,820 and 437,933 respectively. Conclusion The global burden of NHL continues to increase in terms of incident cases, whereas mortality and DALY rates show declining trends. Aging and population growth are the primary drivers. By 2045, NHL will still be a substantial public health challenge. High SDI regions should address workforce shortages and treatment costs, while low SDI regions need investments in early detection and infection control programs.